2016
DOI: 10.1111/1744-9987.12441
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Hemodialysis in Small Children

Abstract: When peritoneal dialysis is inapplicable, chronic hemodialysis (HD) becomes the only available treatment option in small children. Due to small patient size, central venous catheters (CVC) are mainly used for vascular access. Over the past 4 years, four children weighing less than 15 kg received chronic HD in our unit. A total of 848 dialysis sessions were performed. Altogether, 21 catheters were inserted. In all but one occasion, uncuffed catheters were used. Catheter revision was performed 15 times during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Catheter‐related infection rates in similar studies from well‐resourced countries are reportedly between 1.2 and 4/1000 catheter days . In our cohort, this was 1.1/1000 catheter days, which is quite remarkable in a less‐resourced environment.…”
Section: Discussionsupporting
confidence: 59%
“…Catheter‐related infection rates in similar studies from well‐resourced countries are reportedly between 1.2 and 4/1000 catheter days . In our cohort, this was 1.1/1000 catheter days, which is quite remarkable in a less‐resourced environment.…”
Section: Discussionsupporting
confidence: 59%
“…We are currently using 4% citrate for catheter locking at our pediatric dialysis unit, with periodic use of tissue plasminogen activator (t-PA) once weekly, which has been advocated to reduce catheter malfunction as well as CRBSI in adult hemodialysis patients. 15 In small children weighing less than 15 kg, catheter-lock is performed exclusively with t-PA. 4 In contrast, a 30% citrate solution has been used in adult hemodialysis patients at our center since 2005, with excellent infection and catheter malfunction rates.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Thrombosis and infection are the major complications of indwelling dialysis catheters and are particularly common in small children. 3,4 After each hemodialysis session, a locking agent is instilled into the catheter to prevent clotting between treatments, and may even prevent catheterrelated bloodstream infections (CRBSI). Trisodium citrate is now widely replacing heparin for catheter locking and can be potentially superior to heparin in terms of antithrombotic and antimicrobial properties.…”
Section: Introductionmentioning
confidence: 99%
“…Single center data have revealed that greater than 90% of infants receiving chronic HD are accessed via a right or left internal jugular central venous catheter (CVC) 5-8 French in diameter with a median 2.2 catheter changes/patient year and catheter survival times ranging from 1 to 13 months [48,[51][52][53]. Catheters are generally locked with heparin, citrate based solutions, and/or alteplase solutions, based on data from various single center studies with no specific reference to the experience in infants [50,54].…”
Section: Hemodialysismentioning
confidence: 99%